The Latvian Defence Policy of Military Areas in Borderlands - Balodis, Janis; Jakunovs, Mikelis (Richtmann Publishing, 2012)
Planning of military areas by Latvian defence policy is performed, in order to ensure purposeful development of the nationaldefence abilities of Latvia, both on a national level, and within the framework of collective defence. The defence system of Latvia is beingdeveloped in accordance with the geopolitical situation of Latvia, available resources and the military abilities to be applied within theframework of collective security. Latvian defence policy for planning of military areas un borderlands is made by three stages orperspectives. 1) Land use sustainable development - support local planning and economic development objectives. Related with localauthorities. 2) Environmental protection â€“ create development and implementation of the global sustainable development strategyâ€œAgenda 21â€ and the local strategy â€œBaltic Agenda 21â€, Latvia has demonstrated its position regarding environmental protection. Thisstatement is involve from NATO global policy about military area restructuring. 3) Cultural â€“ military heritage perspective. That means ofprotection policy of historical military buildings. It is type how to protect historical property that has relevance and importance in ilustratingthe historical context.